Medical Imaging 2018: Image Processing 2018
DOI: 10.1117/12.2293609
|View full text |Cite
|
Sign up to set email alerts
|

Classification of malignant and benign liver tumors using a radiomics approach

Abstract: Correct diagnosis of the liver tumor phenotype is crucial for treatment planning, especially the distinction between malignant and benign lesions. Clinical practice includes manual scoring of the tumors on Magnetic Resonance (MR) images by a radiologist. As this is challenging and subjective, it is often followed by a biopsy. In this study, we propose a radiomics approach as an objective and non-invasive alternative for distinguishing between malignant and benign phenotypes. T2-weighted (T2w) MR sequences of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…However, two studies used MP‐MRI, including Hectors et al, which first reported that radiomics features identified with MP‐MRI in HCC lesions were significantly different from the normal liver tissue. Additionally, Starmans et al used MP‐MRI to classify malignant and benign liver tumors. Our study further extends MP‐MRI into a new application for use in HCC patients.…”
Section: Discussionsupporting
confidence: 88%
“…However, two studies used MP‐MRI, including Hectors et al, which first reported that radiomics features identified with MP‐MRI in HCC lesions were significantly different from the normal liver tissue. Additionally, Starmans et al used MP‐MRI to classify malignant and benign liver tumors. Our study further extends MP‐MRI into a new application for use in HCC patients.…”
Section: Discussionsupporting
confidence: 88%
“…In patients with >2 lung metastases of ≥10 mm, either the two largest or the two most easily distinguishable lesions were segmented (i.e., two separate lesions were preferred over two adjacent lesions). Using in-house developed software [ 29 ], selected lung metastases were segmented semi-automatically using a lung window for visualization. The result was visually inspected and manually corrected when necessary by an experienced chest radiologist to ensure that the semi-automatic segmentation resembled the manual segmentation.…”
Section: Methodsmentioning
confidence: 99%
“…The lipoma and WDLPS lesions were segmented semiautomatically on the T1 images to indicate the regions of interest (ROIs). All images were segmented independently by either a medical masters student or a PhD candidate with an MD degree.…”
Section: Methodsmentioning
confidence: 99%